(untitled) (MMIT Proceedings, 2024)
The comparative approach, also known as the comparative method, is a valuable tool in teaching philosophy. It helps students gain a deeper understanding of different philosophical traditions and how they have evolved and interacted over time. This article explores the benefits and features of incorporating a comparative approach into philosophy classes.